Corporate Governance, Firm Size, and Organizational Performance: Evidence From Indonesia’s Energy Sector - Fatikha, Nadiya Nur Rahma; Abdullah, Syahriar (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: The main purpose of this study is to examine the relationship between corporate governance, firm size, and financial performance. Methodology: This study employs a quantitative research approach using secondary data obtained from annual reports and audited financial statements of energy companies listed on the Indonesia Stock Exchange. The sample was selected through purposive sampling, and the data were analyzed using multiple linear regression with SPSS. Main Findings: The results indicate that the audit committee has a significant relationship with financial performance, while managerial ownership, institutional ownership, and firm size do not show a significant relationship. Simultaneously, corporate governance and firm size are not significantly associated with financial performance. Research Novelty/Originality: This study contributes to the governance literature by examining corporate governance mechanisms as institutional and organizational structures within the Indonesian energy sector during the 2021–2024 period, providing recent empirical evidence amid economic uncertainty and energy transition dynamics.